Long-Term Integrated Systems of Green Manure and Pasture Significantly Recover the Macrofauna of Degraded Soil in the Brazilian Savannah - Bonini, Carolina dos Santos Batista [UNESP]; Maciel, Thais Monique de Souza [UNESP]; Moreira, Bruno Rafael de Almeida [UNESP]; Chitero, José Guilherme Marques [UNESP]; Henrique, Rodney Lúcio Pinheiro [UNESP]; Alves, Marlene Cristina [UNESP] (MDPI, 2023)
Healthy soil biota is the key to meeting the world population’s growing demand for food, energy, fiber and raw materials. Our aim is to investigate the effect of green manure as a strategy to recover the macrofauna and the chemical properties of soils which have been anthropogenically degraded. The experiment was a completely randomized block design with four replicates. Green manure, Urochloa decumbens, with or without application of limestone and gypsum, composed the integrated systems. The macroorganisms as well as the soil fertility were analyzed after 17 years of a process of soil restoration with the aforementioned systems. The succession of Stizolobium sp. with Urochloa decumbens, with limestone and gypsum, was teeming with termites, beetles and ants. This integrated system presented the most technically adequate indexes of diversity and uniformity. Multivariate models showed a substantial increase in the total number of individuals due to the neutralization of harmful elements and the gradual release of nutrients by limestone and plaster. These conditioners have undergone multiple chemical reactions with the substrate in order to balance it chemically, thus allowing the macroinvertebrates to grow, develop, reproduce and compose their food web in milder microclimates. It was concluded that the integration of green manure together with grass is an economical and environmentally correct strategy to restore the macrofauna properties of degraded soil in the Brazilian savannah.
Keywords: Cajanussp; Canavaliasp; macroorganisms; Urochloa decumbens